Genetic Diversity Study through K-means Clustering in Germplasm Accessions of Green gram [Vigna radiata (L.)] Under Drought Condition - M. S. P, Kanavi; Koler, Prakash; G., Somu; Marappa, N. (International Journal of Bio-resource and Stress Management, 2020)
An experiment was conducted to evaluate 205 green gram germplasm accessions along with five check entries for drought tolerance using augmented design during summer 2015 by imposing drought stress condition. Observations were recorded on 17 quantitative traits. ANOVA revealed high significant differences among germplasm accessions for yield, yield component traits and also for drought tolerance traits. Mean squares attributable to ‘Genotypes vs check entries’ were significant for all the traits except seeds per podand relative water content. Based on K-means clustering, all the 205 germplasm accessions were grouped into seven different clusters. Cluster V was the largest with 38 genotypes followed by cluster I with 36, cluster III and VII with 28, cluster II with 27, cluster IV with 25 and cluster VI with 23 genotypes. The mode of distribution of genotypes coming from different geographical regions into various clusters was at random indicating that the genotypes originating from different agro-climatic regions grouped together into different clusters showing no parallelism between genetic diversity and geographical distribution. The maximum inter cluster distance was recorded between the clusters I and VI (208.17) followed by cluster V and VI (168.52). The minimum inter cluster distance was recorded between the clusters IV and V (45.01) followed by cluster IV and VII (46.97). The maximum intra cluster distance was recorded for the cluster VI (208.17) followed by cluster IV (160.40). The minimum intra cluster distance was recorded for the cluster IV (45.01) followed by cluster V (52.55).